Medidas de enfrentamento dos efeitos econômicos da pandemia Covid-19: Panorama internacional e análise dos casos dos Estados Unidos, do Reino Unido e da Espanha - Claudio Roberto Amitrano; Luís Carlos Garcia de Magalh\~aes; Mauro Santos Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This text presents an international overview of the economic measures adopted to reduce the serious economic effects of the Sars-COV-2 pandemic in three countries: the USA, the United Kingdom and Spain. The analysis is based primarily on government documents that regulated economic policy measures. The various channels through which the health crisis affects the economy are analyzed. On the one hand, there are the supply factors: labor supply, labor productivity and the functioning of production chains. On the other hand, there are demand factors: household consumption, private investment and foreign trade. The third channel concerns the financial factors on demand variables and, mainly, on the degree of liquidity of financial and non-financial companies. The measures adopted in the three countries have as common characteristics the mobilization of large volumes of fiscal and financial resources, the adoption of a wide range of economic policy instruments and the use of sophisticated institutional arrangements in terms of targeting rules and mechanisms for operationalizing the measures adopted.
Keywords: H12; H53; H81; P5; P16; 330; economic crisis; economic policy; public spending; government guarantees; Covid-19